Hiring and Leasing with Nonlinear Prices - Dobbs, Ian M. (Management Science, 1995)
This paper examines the problem of a monopolist setting an optimal nonlinear pricing schedule in the face of consumers of unknown type who arrive randomly over time and self-select a choice of hire period. The major determinant of pricing policy is the customer arrival distribution, with the overall level of price higher than in the atemporal yield management/nonuniform pricing solution by a margin which increases with the average frequency with which potential customers arrive. By contrast, the solution is generally fairly insensitive to variations in the time rate of discount, although there is a tendency for the rate of price discount to increase with increases in the time discount rate.